Trace metal accumulation in the organs of the fish Sarotherodon galilaeus from Alaro stream in Ibadan, Nigeria (2014)
Trace metal accumulation in the organs of the fish Sarotherodon galilaeus from Alaro stream in Ibadan was assessed. A total of 25 fishes were caught in the sampling of Alaro stream. Dissections were carried out using dissecting set to remove the gills, fins, gut (intestine), liver, bones and muscle. Acid digestion was carried out after drying and pulverization of the fish organs. Inductively coupled plasma-mass spectrometer (ICP-MS) was used for the trace metal analyses while bovine liver standard reference material (SRM) from the National Institute of Standards (NIST) was used for quality assurance of the results. This study shows that mean concentration of the following trace metals As, Cd, Cu and Pb in S.galilaeus from the Alaro stream in Ibadan exceeded the World Health Organization (WHO) guideline limits set for most of the organs. This means that Alaro stream is polluted and fish (S.galilaeus) caught from the stream is unfit for human consumption due to the public health consequences posed in consuming such food.